A study on the factor affecting towards credit card usage among workers at Batu Pahat / Roslina Md Noor and Nur Ashikin Ismail - Md Noor, Roslina; Ismail, Nur Ashikin (2013)
This thesis is specially prepared to study the factors affecting credit card usage among workers at Batu Pahat. To complete and make this thesis become stronger and helpful to others, I have collected and analyze much of previous studies and research done by qualified researchers and also few references from various journal and business websites. A questionnaire was used to acquire data from 100 respondents toward workers at Batu Pahat. Convenient sampling is using where the researcher select respondent randomly. The data obtained will be analyzing using Statistical Package for the Social Science (SPSS). There are four independent variables that have been identified for this research. There are credit card attribute, personal attitude & life style, knowledge about credit card and level of income. The factors appear to provide comprehensive understanding that these 54 variables are the factors that influence the credit card usage. The findings create various reasons explaining what factors the best predictor to influence factors is affecting toward credit card usage among workers at Batu Pahat. The various reasons provide scholars with an opportunity to conduct further research in this area.